Hubungan antara Keterobservasian dan Keterkonstruksian Sistem Linier Kontinu Bergantung Waktu - Asfa’ani, Ezhari (Universitas Islam Negeri Imam Bonjol Padang, 2017)
Continuous time-varying linier system is a model which many peoples to find in any applications. This paper to teaching connection of observability and constructibility for continuous time-varying linear system. With algebra method we can proof any theorems to result connection of observability and constructibility for continuous time-varying linear system. Futhermore, we gave any examples for illustration to be valid this theorems and this proof.